2018
DOI: 10.1111/nin.12262
|View full text |Cite
|
Sign up to set email alerts
|

Handling the inpatient's hospital ‘Career’ – Are nurses laying the groundwork for healthy meal and nutritional care transitions?

Abstract: This qualitative study examined hospital nurses' methods in handling meal and nutrition care during inpatient time, with an underlying focus on undernourished older adult. Observations and interviews were used to document nurses' methods through the span of a transition (defined by an entry, passage, and exit). The study finds inconsistencies in care methods due to institutional processes restricting both mealtime care and nutritional logging of information throughout hospitalization. It is concluded that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Some patients found that diet recording could improve the nutritional care and dialog with staff about its importance. This is supported by other studies, suggesting to include patients in the diet registration process [32,43]. One study mentioned that patients' awareness and feeling of responsibility were improved if patients were included in the diet recording.…”
Section: The Main Findings Weresupporting
confidence: 53%
See 2 more Smart Citations
“…Some patients found that diet recording could improve the nutritional care and dialog with staff about its importance. This is supported by other studies, suggesting to include patients in the diet registration process [32,43]. One study mentioned that patients' awareness and feeling of responsibility were improved if patients were included in the diet recording.…”
Section: The Main Findings Weresupporting
confidence: 53%
“…One study mentioned that patients' awareness and feeling of responsibility were improved if patients were included in the diet recording. Furthermore, it would help nurses remember that the diet should be registered [32]. Other studies have found that developing standards for nurses and teaching them about nutritional care may improve nutritional care [30,44].…”
Section: The Main Findings Werementioning
confidence: 99%
See 1 more Smart Citation